Dose escalation and switching of biologics in ulcerative colitis: a systematic literature review in real-world evidence. (2nd November 2019) - Gemayel, Nathalie C.; Rizzello, Eugenio; Atanasov, Petar; Wirth, Daniel; Borsi, Andras
Abstract: Background: Biologics used to treat ulcerative colitis (UC) may lose their effect over time, requiring patients to undergo dose escalation or treatment switching, and systematic literature reviews of real-world evidence on these topics are lacking. Aim: To summarize the occurrence and outcomes of dose escalation and treatment switching in UC patients in real-world evidence. Methods: Studies were searched through MEDLINE, MEDLINE IN PROCESS, Embase and Cochrane (2006–2017) as well as proceedings from three major scientific meetings. Results: In total, 41 studies were included in the review among which 35 covered dose escalation and 12 covered treatment switching of biologics. Tumor necrosis factor antagonist (anti-TNF) escalation for all patients included at induction ranged from 5% (6 months) to 50% (median 0.67 years) and 15.2% to 70.8% (8 weeks) for anti-TNF induction responders. Mean/median time to dose escalation on anti-TNF ranged from 1.84 to 11 months. The most common switching pattern, infliximab → adalimumab, occurred in 3.8% (median 5.6 years) to 25.5% (mean 3.3 years) of patients. Conclusions: Dose escalation and treatment switching of biologics may be considered as indicators of suboptimal therapy suggesting a lack of long-term remission and response under current therapies.